Glycinergic synapse development, plasticity, and homeostasis in zebrafish - Ganser, Lisa R.; Dallman, Julia (Frontiers in Molecular Neuroscience, 2009)
The zebrafish glial glycine transporter 1 (GlyT1) mutant provides an animal model in which homeostatic plasticity at glycinergic synapses restores rhythmic motor behaviors. GlyT1 mutants, initially paralyzed by the build-up of the inhibitory neurotransmitter glycine, stage a gradual recovery that is associated with reductions in the strength of evoked glycinergic responses. Gradual motor recovery suggests sequential compensatory mechanisms that culminate in the down-regulation of the neuronal glycine receptor. However, how motor recovery is initiated and how other forms of plasticity contribute to behavioral recovery are still outstanding questions that we discuss in the context of (1) glycinergic synapses as they function in spinal circuits that produce rhythmic motor behaviors, (2) the proteins involved in regulating glycinergic synaptic strength, (3) current models of glycinergic synaptogenesis, and (4) plasticity mechanisms that modulate the strength of glycinergic synapses. Concluding remarks (5) explore the potential for distinct plasticity mechanisms to act in concert at different spatial and temporal scales to achieve a dynamic stability that results in balanced motor behaviors.